Oral health, the perspective of the inmate and the context of vulnerability - Cristina Berger FADEL; Lígia Maria VALENTIM; Thaís Marília FILLUS; Jean Érick LANGOSKI; Danielle BORDIN
AbstractIntroductionThe increase in prison populations is a phenomenon which is systematically rising throughout the world, leading to overcrowding of prisons, which has direct consequences on the health conditions of the individuals.ObjectiveTo explore the relationship among oral health, the life path and the perception of subjects in a vulnerability context.Material and methodThis is a qualitative study, developed with inmates in a State Penitentiary. To obtain and process the data, individual interviews and the Thematic Content Analysis technique were used.ResultThe interviewees showed limited perception of the process of oral health and disease fostered by the experiences of relatives and by knowledge acquired in the street or from the media. The life path in prison seemed to have little influence on this understanding. However, the prison experience influenced the oral condition of the inmates by facilitating access to dental service, oral hygiene materials and the improvement in their health knowledge and habits. The oral health results presented were, generally, in agreement with so-called common sense and with studies developed in socially similar populations.ConclusionThus, considering the limitations imposed by the way data were collected, in prison and in a vulnerability context; a non-harmful influence on the condition studied regarding the oral health of inmates is suggested.